Multilayer intensity modulated contact interventional radiotherapy (brachytherapy): Stretching the therapeutic window in skin cancer - Fionda, Bruno; Placidi, Elisa; Rosa, Enrico; Lancellotta, Valentina; Stimato, Gerardina; De Angeli, Martina; Ciardo, Francesco Giuseppe; Cornacchione, Patrizia; Siebert, Frank-Andre; Tagliaferri, Luca; Indovina, Luca (Journal of Contemporary Brachytherapy, 2023)
Interventional radiotherapy (IRT, brachytherapy) is a highly effective treatment method for non-melanoma skin cancer (NMSC). Traditionally, the maximum depth of NMSC lesions considered eligible for contact IRT was 5 mm; however, following several national surveys and recent recommendations, such cut-off, lesions thicker than 5 mm may be treated by contact IRT. The use of image guidance in defining the actual depth in treating NMSC to correctly identify clinical target volume (CTV) and prevent unnecessary toxicity is of paramount importance. The aim of the paper was to describe a multilayer arrangement of catheters to treat NMSC lesions thicker than 5 mm, thus proposing an example of dynamic intensity modulated IRT, using different catheter-to-skin distance of sources to reach the best CTV coverage and maximally reduce the excess of dose to the skin.